Perovskite solar cell, preparation method thereof and photovoltaic module

By preparing the cross -layer of the multi -layer height refractive index layer of the cross layer of the cross -layer of the mesolecular battery to the glass base of the solar cell, the UV blocking layer of the material layer of the material layer of the perovskite solar cell is solved, and its ultraviolet stability has been significantly improved. And photoelectric conversion efficiency.

CN119364984APending Publication Date: 2025-01-24RENSHUO SOLAR ENERGY (SUZHOU) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411494048.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The degradation problem of perovskite solar cells under ultraviolet light leads to poor stability, affecting the commercialization process of their applications.

Method used

The UV blocking layer of the film stack structure on the glass base is coordinated by the multi -layer high refractive index layer and the multi -layer low refractive index material layer of the multi -layer and high refractive index material layer set by cross -layer stack settings. Essence

Benefits of technology

It significantly improves the ultraviolet light stability of the perovskite solar cells, enhances the spectral response, so that the ultraviolet light reflectance of the device reaches more than 99 %, and improves the photoelectric conversion efficiency and high humidity and high heat stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119364984A_ABST
    Figure CN119364984A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite solar cell, a preparation method thereof and a photovoltaic module. The perovskite solar cell comprises a glass substrate, a UV barrier layer, a transparent conductive layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer and a back electrode layer which are arranged in a stacked manner. The UV blocking layer is of a film stack structure, and the film stack structure comprises a plurality of high-refractive-index material layers and a plurality of low-refractive-index material layers which are arranged in a crossed and stacked mode. According to the invention, the UV barrier layer with a film stack structure is prepared on the glass substrate, and the degradation of perovskite under ultraviolet light is effectively inhibited by means of the cooperation of the plurality of high-refractive-index material layers and the plurality of low-refractive-index material layers which are arranged in a crossed and stacked manner, so that the ultraviolet light reflectivity of the device reaches 99% or above, and the performance of the device is improved. Meanwhile, the photoelectric conversion efficiency and the high-humidity and high-heat stability of the device are further improved, and preparation of a large-area device is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solar cells, and in particular relates to a perovskite solar cell and a preparation method thereof, and a photovoltaic module. Background Art

[0002] Organic and inorganic halide perovskite semiconductor materials have the advantages of high absorption coefficient, large carrier mobility, adjustable band gap and bipolar carrier transport. The relatively low defect density and excellent defect tolerance make them have great potential in the photovoltaic field. At present, the highest photoelectric conversion efficiency of single-junction perovskite solar cells (PSCs) has reached 26.1%, which is close to the highest efficiency of crystalline silicon solar cells and has the advantages of theoretical low cost and easy preparation. It is one of the most active research directions in the current materials and energy fields. However, as a competitor to traditional commercial solar photovoltaic products, perovskite solar cells must also be as stable as them. Their long-term stability remains the most important challenge facing the commercialization of emerging photovoltaic technologies.

[0003] In terms of stability issues, solving the problems of ultraviolet (UV), heat and interface contact instability is of utmost importance. Among them, UV can cause great damage to PSCs, directly damaging the interface between perovskite and substrate, resulting in poor hole extraction and accelerated migration of A-site cations, causing perovskite degradation and shortening its lifespan; and, because the defects generated by UV act as non-radiative recombination sites, they will accelerate the degradation process, reduce device efficiency and weaken the stability of solar cells.

[0004] Therefore, in order to avoid the influence of UV light on PSCs, a series of works have been devoted to using new ETLs (such as BaSnO3) to improve the UV stability of PSCs in recent years, as well as adding Cl - and Br - Plasma to increase Pb 2+ The bonding ability of ions and halogens can effectively improve the decomposition barrier of perovskite. In addition, at room temperature, a UV absorption layer formed by multifunctional fluorinated photosensitive polymers, cesium bromide, aminofullerene or antimony sulfide is covered on the surface of the perovskite cell device to reduce the damage of ultraviolet rays to the cell device, thereby improving the device's resistance to ultraviolet radiation. However, compared with the environmental stability requirements of silicon-based solar cells, the current stability of PSCs is still far from enough, and the poor UV stability has not been fundamentally and effectively solved.

[0005] Therefore, how to effectively inhibit the degradation of perovskite under ultraviolet light and further improve the ultraviolet light stability of perovskite solar cells is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a perovskite solar cell and a preparation method thereof and a photovoltaic module. The present invention prepares a UV blocking layer of a film stack structure on a glass substrate, and then cooperates with multiple layers of high refractive index material layers and multiple layers of low refractive index material layers arranged in a cross-stacked manner, which not only adjusts the defects, but also effectively inhibits the degradation of perovskite under ultraviolet light, enhances the spectral response, and makes the ultraviolet light reflectivity of the device reach more than 99%, significantly improves the ultraviolet light stability of the device, and further improves the photoelectric conversion efficiency and high humidity and high heat stability of the device, which is conducive to the preparation of large-area devices.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a perovskite solar cell, the perovskite solar cell comprising a stacked glass substrate, a UV blocking layer, a transparent conductive layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer and a back electrode layer;

[0009] The UV blocking layer is a film stack structure, which includes a plurality of high-refractive index material layers and a plurality of low-refractive index material layers that are cross-stacked.

[0010] The present invention prepares a UV blocking layer of a film stack structure on a glass substrate, and then cooperates with multiple layers of high refractive index material layers and multiple layers of low refractive index material layers that are cross-stacked, which not only adjusts the defects but also effectively inhibits the degradation of perovskite under ultraviolet light and enhances the spectral response, so that the ultraviolet light reflectivity of the device reaches more than 99%, significantly improving the ultraviolet light stability of the device, and further improving the photoelectric conversion efficiency and high humidity and high heat stability of the device, which is conducive to the preparation of large-area devices.

[0011] It should be noted that the adjacent high refractive index material layer and low refractive index material layer form a refractive index matching group, recorded as an interference film. Such an interference film can better control the transmittance in the visible light wavelength range and make the reflection of ultraviolet light reach more than 99%, avoiding perovskite degradation, thereby improving the stability of the device.

[0012] Preferably, the total number of layers of the membrane stack structure is 10-30 layers, for example, it can be 10 layers, 12 layers, 14 layers, 16 layers, 18 layers, 20 layers, 22 layers, 24 layers, 26 layers, 28 layers or 30 layers.

[0013] In the present invention, if the total number of layers of the membrane stack structure is too small, the barrier effect will be poor; if the total number of layers of the membrane stack structure is too large, the cost expenditure will increase, and due to the absorption, scattering and other losses of the membrane layer, after the membrane system reaches a certain number of layers, continuing to increase the number of membrane layers will no longer improve the barrier effect.

[0014] Preferably, the refractive index of each layer of the high refractive index material is 1.9-2.7, for example, it may be 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5 or 2.6.

[0015] Preferably, the refractive index of each layer of the low refractive index material is 1.35-1.6, for example, it may be 1.35, 1.4, 1.45, 1.5, 1.55 or 1.6.

[0016] In the present invention, the high refractive index material layer with a refractive index of 1.9-2.6 and the low refractive index material layer with a refractive index of 1.35-1.6 cooperate with each other to better reverse the phase of light of a specific wavelength, thereby achieving selective reflection of light of a specific wavelength to achieve the purpose of controlling light propagation.

[0017] Preferably, in the film stack structure, the material layers on the side close to the glass substrate and the side close to the transparent conductive layer are both high refractive index material layers.

[0018] In the present invention, the above structure can make the light reflect on the surface of the film, thereby achieving the effect of controlling the propagation of light.

[0019] Preferably, the thickness of each layer of the high refractive index material is 10-300 nm, for example, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm or 300 nm.

[0020] In the present invention, if the thickness of each high refractive index material layer is too thin or too thick, the barrier effect will be reduced, so that the degradation of perovskite under ultraviolet light cannot be effectively suppressed.

[0021] Preferably, the thickness of each layer of the low refractive index material is 10-300 nm, for example, 10 nm, 50 nm, 100 nm, 150 nm, 200 nm, 250 nm or 300 nm.

[0022] In the present invention, if the thickness of each low refractive index material layer is too thin or too thick, the barrier effect will be reduced, so that the degradation of perovskite under ultraviolet light cannot be effectively suppressed.

[0023] Preferably, the material of each high refractive index material layer includes any one of metal oxide, metal sulfide or nitride, or a combination of at least two of them.

[0024] It should be noted that the present invention does not specifically limit the type of metal oxide, and illustratively, it may be titanium oxide, niobium pentoxide, zinc oxide, calcium oxide, tantalum pentoxide, zirconium oxide, chromium oxide, antimony oxide or lead oxide, etc.; the present invention does not specifically limit the type of metal sulfide, and illustratively, it may be titanium sulfide, chromium sulfide, zinc sulfide, cobalt sulfide, antimony sulfide, lead sulfide, lanthanum sulfide, cerium sulfide, tungsten sulfide or zirconium sulfide, etc.; the present invention does not specifically limit the type of nitride, and illustratively, it may be silicon nitride or aluminum nitride, etc.

[0025] Preferably, the material of each low refractive index material layer includes any one of cryolite, lanthanum fluoride, magnesium fluoride, sodium aluminum hexafluoride or SiO2, or a combination of at least two thereof.

[0026] Preferably, the glass substrate comprises ultra-clear float glass.

[0027] It should be noted that ultra-clear float glass refers to ultra-clear glass that has all the processability of high-quality float glass, and has excellent physical, mechanical and optical properties. It can be subjected to various deep processing like other high-quality float glass, such as tempering, coating, glaze, hot bending, lamination, hollow assembly, etc.

[0028] Preferably, the material of the transparent conductive layer includes any one of ITO (tin-doped indium oxide), AZO (aluminum-doped zinc oxide), IWO (tungsten-doped indium oxide) or IZO (zinc-doped indium oxide), or a combination of at least two of them.

[0029] Preferably, the thickness of the transparent conductive layer is 15-200 nm, for example, 15 nm, 30 nm, 50 nm, 65 nm, 80 nm, 100 nm, 150 nm or 200 nm.

[0030] Preferably, the back electrode layer is a metal electrode.

[0031] It should be noted that the present invention does not specifically limit the type of the metal electrode. Exemplarily, the metal electrode includes any one of a Cu electrode, an Ag electrode or an Au electrode, or a combination of at least two of them.

[0032] Preferably, the thickness of the back electrode layer is 15-100 nm, for example, 15 nm, 30 nm, 50 nm, 65 nm, 80 nm or 100 nm.

[0033] Preferably, the first charge transport layer and the second charge transport layer transport charges of opposite electrical properties.

[0034] Preferably, the first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer.

[0035] Preferably, the thickness of the hole transport layer is 15-45 nm, for example, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm or 45 nm.

[0036] Preferably, the thickness of the electron transport layer is 5-50 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.

[0037] Preferably, the material of the hole transport layer includes any one or a combination of at least two of vanadium oxide, tungsten oxide, magnesium oxide, cuprous thiocyanate (CuSCN), cuprous iodide (CuI), copper oxide (CuO), cuprous oxide (Cu2O), nickel oxide (NiO), vanadium pentoxide (V2O5), molybdenum trioxide (MoO3), Spiro-OMeTAD, P3HT, PTAA or PEDOT:PSS.

[0038] Preferably, the material of the electron transport layer includes TiO2, SnO2, ZTO (zinc-doped tin oxide), CdS, C 60 , ZMO (magnesium-doped zinc oxide), ZnO, IWO (tungsten-doped indium oxide) or PCBM, or a combination of at least two of them.

[0039] Preferably, the chemical formula of the perovskite absorber layer is ABX3, wherein A includes any one or a combination of at least two of formamidinium ions, methylamine ions or cesium ions, B includes lead ions, and X is a halogen ion. For example, it can be FAPbI3, MAPbI3, FA x Cs 1-x PbI3、FA x Cs 1-x PbI y Br 3-y 、FACsMAPbI y Br 3-y Or CsPbI3, etc., wherein the value range of x is 0.05-0.2, for example, it can be 0.05, 0.1, 0.13, 0.15, 0.18 or 0.2, etc., and the value range of y is 0-3, for example, it can be 0, 1, 2 or 3, etc.

[0040] Preferably, the thickness of the perovskite absorption layer is 300-500 nm, for example, 300 nm, 400 nm or 500 nm.

[0041] In a second aspect, the present invention provides a method for preparing a perovskite solar cell as described in the first aspect, the preparation method comprising the following steps:

[0042] A UV blocking layer, a transparent conductive layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer and a back electrode layer are sequentially deposited on a glass substrate to obtain the perovskite solar cell.

[0043] Preferably, the deposition method of the UV blocking layer includes any one of electron beam evaporation, metal organic chemical vapor epitaxy, plasma enhanced vapor deposition, magnetron sputtering, atomic layer deposition, reactive plasma deposition, solution method or vacuum thermal evaporation, or a combination of at least two thereof.

[0044] It should be noted that the power source used in the magnetron sputtering method includes a radio frequency power source, a DC pulse power source, a medium frequency power source or a DC power source.

[0045] Preferably, the deposition methods of the first charge transport layer and the second charge transport layer independently include any one of magnetron sputtering, vacuum evaporation, solution deposition, atomic layer deposition or reactive plasma deposition, or a combination of at least two thereof.

[0046] Preferably, the deposition method of the transparent conductive layer includes reactive plasma deposition and / or magnetron sputtering.

[0047] Preferably, the deposition method of the back electrode layer includes vacuum thermal evaporation and / or magnetron sputtering.

[0048] Preferably, the preparation method of the perovskite absorption layer comprises any one of a solution method, a doctor blade method, a spraying method, an inkjet printing method, a printing method or a vacuum solution two-step method.

[0049] Preferably, in the scraping method, the scraping rate is 10-15 mm / s, for example, it can be 10 mm / s, 11 mm / s, 12 mm / s, 13 mm / s, 14 mm / s or 15 mm / s.

[0050] In a third aspect, the present invention provides a photovoltaic module, wherein the photovoltaic module comprises the perovskite solar cell as described in the first aspect.

[0051] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The present invention prepares a UV blocking layer of a film stack structure on a glass substrate, and then uses a cross-stacked multi-layer high-refractive index material layer and a multi-layer low-refractive index material layer to cooperate with each other, which not only adjusts the defects, but also effectively inhibits the degradation of perovskite under ultraviolet light and enhances the spectral response, so that the ultraviolet light reflectivity of the device reaches more than 99%, significantly improving the ultraviolet light stability of the device, and further improving the photoelectric conversion efficiency and high-humidity and high-heat stability of the device, which is conducive to the preparation of large-area devices.

[0054] (2) The preparation method provided by the present invention has the advantages of low cost and scalability, and can achieve simultaneous improvement of short-circuit current and fill factor, which is conducive to obtaining high-efficiency and high-stability perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 Schematic diagram of the structure of the perovskite solar cell prepared in Example 1 of the present invention.

[0056] Among them, 1-ultra-clear float glass; 2-UV blocking layer; 3-transparent conductive layer; 4-hole transport layer; 5-perovskite absorption layer; 6-electron transport layer; 7-buffer layer; 8-metal electrode. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] Example 1

[0059] This embodiment provides a perovskite solar cell, and its structural schematic diagram is as follows Figure 1 As shown, the perovskite solar cell comprises a stacked ultra-white float glass 1, a UV blocking layer 2, a transparent conductive layer 3, a hole transport layer 4, a perovskite absorption layer 5, an electron transport layer 6, a buffer layer 7 and a metal electrode 8;

[0060] The UV blocking layer 2 is a film stack structure, which is stacked in sequence along a direction away from the glass substrate. H represents a high refractive index material layer made of titanium pentoxide, and L represents a low refractive index material layer made of silicon dioxide. The thickness of each layer is 23.1nm / 48.4nm / 32.3nm / 52.6nm / 37.5nm / 44.7nm / 39.6nm / 52.8nm / 27.3nm / 70.2nm / 30.5nm / 50.7nm / 32.5nm / 74nm / 11.1nm, and the refractive index of each layer is 2.66 / 1.48 / 2.66 / 1.48 / 2.66 / 1.48 / 2.66 / 1.48 / 2.66 / 1.48 / 2.66 / 1.48 / 2.66 / 1.48 / 2.66;

[0061] The material of the transparent conductive layer 3 is ITO with a thickness of 180 nm; the hole transport layer 4 is a nickel oxide layer with a thickness of 15 nm; the chemical formula of the perovskite absorption layer 5 is Cs 0.1 FA 0.9 PbI3, with a thickness of 500nm; the electron transport layer 6 includes a stacked arrangement of C 60 layer and IWO layer, C 60 The thickness of the layer is 12nm, and the thickness of the IWO layer is 50nm; the material of the buffer layer 7 is ITO, and the thickness is 30nm; the metal electrode 8 is a Cu electrode, and the thickness is 60nm.

[0062] This embodiment also provides a method for preparing the above-mentioned perovskite solar cell, and the preparation method comprises the following steps:

[0063] (1) Ultra-clear float glass 1 is ultrasonically cleaned with glass cleaning agent and deionized water respectively, and then fully dried in an oven at 100° C. This process is repeated three times, and ultra-clear float glass 1 is subjected to ultraviolet-ozone treatment for 30 minutes. After the treatment, the ultra-clear float glass is placed in an electron beam evaporation device for coating;

[0064] (2) The vacuum degree of the electron beam evaporation equipment is less than 1×10 -3 Pa, setting an argon-oxygen mixed gas and turning on an ion source and a neutralizer, performing electron beam evaporation coating on the ultra-clear float glass 1, and sequentially depositing HLHLHLHLHLHLHLH of different thicknesses, wherein H represents a high-refractive-index material layer whose material is titanium pentoxide, and L represents a low-refractive-index material layer whose material is silicon dioxide, to obtain a UV blocking layer 2;

[0065] (3) The vacuum degree of the magnetron sputtering equipment is less than 1×10 -3When Pa, high-purity argon and argon-oxygen mixed gas are provided and a direct current power supply is used to perform magnetron sputtering of ITO on the UV blocking layer 2 to obtain a transparent conductive layer 3;

[0066] (4) In the same device as step (3), a radio frequency power source is used in a vacuum of less than 1×10 -3 When Pa, high-purity argon and argon-oxygen mixed gas are provided and magnetron sputtering of nickel oxide is performed on the surface of the transparent conductive layer 3 to obtain the hole transport layer 4;

[0067] (5) Take an appropriate amount of 1.1 mol / L perovskite precursor solution and scrape it on the surface of the hole transport layer 4, then blow off the excess solvent with nitrogen, and then anneal at 70°C for 2 min on a heating table, and then anneal at 110°C for 40 min to form a 2D perovskite absorption layer 5, whose chemical formula is Cs 0.1 FA 0.9 PbI3;

[0068] (6) Using vacuum evaporation method, the vacuum degree is less than 5×10 -4 Pa under the condition of C deposition on the surface of the perovskite absorber layer 5 60 layer, and then the IWO layer is deposited by reactive plasma deposition, wherein C 60 The deposition rate of the layer is The Gun (i.e., ion gun) current of IWO is 100A, and an electron transport layer 6 is obtained;

[0069] (7) Using radio frequency magnetron sputtering, the vacuum degree is less than 5×10 -4 Under the condition of Pa, an ITO layer and a Cu electrode are sequentially deposited on the surface of the electron transport layer 6 to obtain the perovskite solar cell.

[0070] Example 2

[0071] This embodiment provides a perovskite solar cell, which includes a stacked ultra-white float glass, a UV blocking layer, a transparent conductive layer, a hole transport layer, a perovskite absorption layer, an electron transport layer, a buffer layer and a metal electrode;

[0072] The UV blocking layer is a film stack structure, and the film stack structure is sequentially stacked with HLHLHLHLHLHLHLHLHLHLHLHLH along a direction away from the glass substrate, wherein H represents a high refractive index material layer whose material is titanium pentoxide, and L represents a low refractive index material layer whose material is magnesium fluoride, and the thickness of each layer is 6.1nm / 80.8nm / 15.9nm / 72.4nm / 26nm / 56.7nm / 34.4nm / 53.6nm / 30nm / 65nm / 31.4nm / 49.8nm / 37.8nm / 58.9nm / 26 .4nm / 64.8nm / 35.7nm / 48.7nm / 30.4nm / 71.4nm / 27nm / 49.9nm / 33.5nm / 74.5nm / 8.7nm, the refractive index of each layer is 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66 / 1.39 / 2.66;

[0073] The material of the transparent conductive layer is ITO with a thickness of 180nm; the hole transport layer is a nickel oxide layer with a thickness of 15nm; the chemical formula of the perovskite absorption layer is Cs 0.1 FA 0.9 PbI3, with a thickness of 500nm; the electron transport layer includes a stacked arrangement of C 60 layer and IWO layer, C 60 The thickness of the layer is 12nm, the thickness of the IWO layer is 50nm; the material of the buffer layer is ITO, with a thickness of 30nm; the metal electrode is a Cu electrode, with a thickness of 60nm.

[0074] This embodiment also provides a method for preparing the above-mentioned perovskite solar cell, and the preparation method comprises the following steps:

[0075] (1) Ultra-clear float glass is ultrasonically cleaned with glass cleaning agent and deionized water respectively, and then fully dried in an oven at 100° C. This process is repeated three times, and ultra-clear float glass is subjected to UV-ozone treatment for 30 minutes. After the treatment, the ultra-clear float glass is placed in an electron beam evaporation device for coating;

[0076] (2) The vacuum degree of the electron beam evaporation equipment is less than 1×10 -3Pa, setting an argon-oxygen mixed gas, turning on an ion source and a neutralizer, performing electron beam evaporation coating on the ultra-clear float glass, and sequentially depositing HLHLHLHLHLHLHLHLHLHLHLHLHL of different thicknesses, wherein H represents a high-refractive-index material layer whose material is titanium pentoxide, and L represents a low-refractive-index material layer whose material is magnesium fluoride, to obtain a UV blocking layer;

[0077] (3) The vacuum degree of the magnetron sputtering equipment is less than 1×10 -3 When Pa, high-purity argon and argon-oxygen mixed gas are set and a direct current power supply is used to perform magnetron sputtering of ITO on the UV blocking layer to obtain a transparent conductive layer;

[0078] (4) In the same device as step (3), a radio frequency power source is used in a vacuum of less than 1×10 -3 When Pa, high-purity argon and argon-oxygen mixed gas are provided and magnetron sputtering of nickel oxide is performed on the surface of the transparent conductive layer to obtain a hole transport layer;

[0079] (5) Take an appropriate amount of 1.1 mol / L perovskite precursor solution and scrape it on the surface of the hole transport layer, then blow off the excess solvent with nitrogen, and then anneal it on a heating table at 70°C for 2 min, and then anneal it at 110°C for 40 min to form a 2D perovskite absorption layer, whose chemical formula is Cs 0.1 FA 0.9 PbI3;

[0080] (6) Using vacuum evaporation method, the vacuum degree is less than 5×10 -4 C is deposited on the surface of the perovskite absorber under the condition of Pa. 60 layer, and then the IWO layer is deposited by reactive plasma deposition, wherein C 60 The deposition rate of the layer is The Gun (i.e., ion gun) current of IWO is 100A to obtain an electron transport layer;

[0081] (7) Using radio frequency magnetron sputtering, the vacuum degree is less than 5×10 -4 Under the condition of Pa, an ITO layer and a Cu electrode are sequentially deposited on the surface of the electron transport layer to obtain the perovskite solar cell.

[0082] Example 3

[0083] This embodiment provides a perovskite solar cell, which includes a stacked ultra-white float glass, a UV blocking layer, a transparent conductive layer, a hole transport layer, a perovskite absorption layer, an electron transport layer, a buffer layer and a metal electrode;

[0084] The UV blocking layer is a film stack structure, and the film stack structure is sequentially stacked with HLHLHLHLHLHLH along a direction away from the glass substrate, wherein H represents a high refractive index material layer made of niobium pentoxide, and L represents a low refractive index material layer made of silicon dioxide, and the thickness of each layer is 125.8nm / 41.2nm / 31.6nm / 62.8nm / 34.5nm / 53.4nm / 33.7nm / 61.3nm / 34nm / 53nm / 35.7nm / 69.9nm / 13.2nm, and the refractive index of each layer is 2.56 / 1.48 / 2.56 / 1.48 / 2.56 / 1.48 / 2.56 / 1.48 / 2.56 / 1.48 / 2.56;

[0085] The material of the transparent conductive layer is ITO with a thickness of 180nm; the hole transport layer is a nickel oxide layer with a thickness of 15nm; the chemical formula of the perovskite absorption layer is Cs 0.1 FA 0.9 PbI3, with a thickness of 500nm; the electron transport layer includes a stacked arrangement of C 60 layer and IWO layer, C 60 The thickness of the layer is 12nm, the thickness of the IWO layer is 50nm; the material of the buffer layer is ITO, with a thickness of 30nm; the metal electrode is a Cu electrode, with a thickness of 60nm.

[0086] This embodiment also provides a method for preparing the above-mentioned perovskite solar cell, and the preparation method comprises the following steps:

[0087] (1) Ultra-clear float glass is ultrasonically cleaned with glass cleaning agent and deionized water respectively, and then fully dried in an oven at 100° C. This process is repeated three times, and ultra-clear float glass is subjected to UV-ozone treatment for 30 minutes. After the treatment, the ultra-clear float glass is placed in an electron beam evaporation device for coating;

[0088] (2) The vacuum degree of the electron beam evaporation equipment is less than 1×10 -3 Pa, setting an argon-oxygen mixed gas, turning on an ion source and a neutralizer, performing electron beam evaporation coating on the ultra-clear float glass, and sequentially depositing HLHLHLHLHLHLH of different thicknesses, wherein H represents a high-refractive-index material layer whose material is niobium pentoxide, and L represents a low-refractive-index material layer whose material is silicon dioxide, to obtain a UV blocking layer;

[0089] (3) The vacuum degree of the magnetron sputtering equipment is less than 1×10 -3 When Pa, high-purity argon and argon-oxygen mixed gas are set and a direct current power supply is used to perform magnetron sputtering of ITO on the UV blocking layer to obtain a transparent conductive layer;

[0090] (4) In the same device as step (3), a radio frequency power source is used in a vacuum of less than 1×10 -3 When Pa, high-purity argon and argon-oxygen mixed gas are provided and magnetron sputtering of nickel oxide is performed on the surface of the transparent conductive layer to obtain a hole transport layer;

[0091] (5) Take an appropriate amount of 1.1 mol / L perovskite precursor solution and scrape it on the surface of the hole transport layer, then blow off the excess solvent with nitrogen, and then anneal it on a heating table at 70°C for 2 min, and then anneal it at 110°C for 40 min to form a 2D perovskite absorption layer, whose chemical formula is Cs 0.1 FA 0.9 PbI3;

[0092] (6) Using vacuum evaporation method, the vacuum degree is less than 5×10 -4 C is deposited on the surface of the perovskite absorber under the condition of Pa. 60 layer, and then the IWO layer is deposited by reactive plasma deposition, wherein C 60 The deposition rate of the layer is The Gun (ion gun) current of IWO is 100A to obtain an electron transport layer;

[0093] (7) Using radio frequency magnetron sputtering, the vacuum degree is less than 5×10 -4 Under the condition of Pa, an ITO layer and a Cu electrode are sequentially deposited on the surface of the electron transport layer to obtain the perovskite solar cell.

[0094] Example 4

[0095] The difference between this embodiment and embodiment 1 is that the film stack structure is stacked with HLHLHLH in sequence along the direction away from the glass substrate, and the thickness of each layer is 23.1nm / 48.4nm / 32.3nm / 52.6nm / 37.5nm / 44.7nm / 39.6nm respectively.

[0096] The rest of the preparation methods and parameters were the same as those in Example 1.

[0097] Example 5

[0098] The difference between this embodiment and embodiment 1 is that the membrane stack structure is stacked in sequence along the direction away from the glass substrate, and the thickness of each layer is 6.6nm / 77.7nm / 35.2nm / 18.8nm / 16.9nm / 14.4nm / 36nm / 40.5nm / 41.8nm / 37.4nm / 37.9nm / 57.9nm / 17.7nm / 20.9nm / 10.6nm / 44.7nm / 42.3nm / 33.7nm / 41.5nm / 43.2nm / 36.8nm / 31nm / 38.5nm / 21.5nm / 32.9nm / 32nm / 34.6nm / 40.8nm / 31.7nm / 51.1nm / 14.3nm respectively.

[0099] The rest of the preparation methods and parameters were the same as those in Example 1.

[0100] Example 6

[0101] The difference between this embodiment and embodiment 1 is that the material of the high refractive index material layer is replaced by yttrium oxide, and the thickness of each layer is 24.3nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 48.6nm / 30.5nm / 24.3nm, and the refractive index of each H is less than 1.9.

[0102] The rest of the preparation methods and parameters were the same as those in Example 1.

[0103] Example 7

[0104] The difference between this embodiment and embodiment 1 is that the material of the low refractive index material layer is aluminum oxide, and the thickness of each layer is 16.9nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 26.7nm / 33.8nm / 16.9nm, and the refractive index of each L is greater than 1.6.

[0105] The rest of the preparation methods and parameters were the same as those in Example 1.

[0106] Comparative Example 1

[0107] The difference between this comparative example and Example 1 is that no UV blocking layer is provided, that is, step (2) is not performed.

[0108] The rest of the preparation methods and parameters were the same as those in Example 1.

[0109] Comparative Example 2

[0110] The difference between this comparative example and Example 1 is that L is not provided in the membrane stack structure, that is, the UV blocking layer is a high refractive index material layer with a thickness of 233.9 nm.

[0111] The rest of the preparation methods and parameters were the same as those in Example 1.

[0112] Comparative Example 3

[0113] The difference between this comparative example and Example 1 is that H is not provided in the membrane stack structure, that is, the UV blocking layer is a low refractive index material layer with a thickness of 393.4 nm.

[0114] The rest of the preparation methods and parameters were the same as those in Example 1.

[0115] Performance Testing

[0116] The perovskite solar cells provided in the above embodiments and comparative examples were subjected to photoelectric performance tests and ultraviolet light stability tests.

[0117] Among them, the test parameters of the photoelectric performance test include open circuit voltage (Voc), short circuit current (Jsc), fill factor (FF) and photoelectric conversion efficiency (PCE). The test method includes: using a solar simulator to emit a standard sunlight (spectrum AM1.5G, incident power 100mW / cm2, temperature 25°C), photoelectric conversion efficiency = (open circuit voltage × short circuit current × fill factor) / battery area × light amplitude × 100%.

[0118] The UV stability test method includes: in a UV aging box (0.63W / m 2 @340nm) conditions, and record the changes in the photoelectric conversion efficiency of the tested perovskite solar cells.

[0119] The above test results are shown in Table 1.

[0120] Table 1

[0121]

[0122] analyze:

[0123] As can be seen from the above table, Examples 1-3 use a UV blocking layer made of overlapping high and low refractive index materials on ultra-white float glass, which improves the efficiency of the device and the intrinsic stability of the perovskite absorption layer. While maintaining a high photoelectric conversion efficiency, the photoelectric conversion efficiency attenuation after UV aging is more than 20% different from that of Comparative Example 1. Although there are also different degrees of attenuation in Examples 1-3, they are all within 5%, and Example 2 is slightly improved; secondly, the obvious difference in the initial short-circuit current reflects the high visible light transmittance of the UV blocking layer, and ultimately reflects an efficiency difference of about 1% in the initial device conversion efficiency. The attenuation of the short-circuit current in the data of Comparative Example 1 indicates that the carrier transmission capacity decreases and as the ultraviolet irradiation time increases, the corresponding resistance and defect density inside the battery increase rapidly.

[0124] It can be seen from Example 1 and Examples 4-5 that if the total number of layers of the membrane stack structure is too small, the UV blocking effect is poor; if the total number of layers of the membrane stack structure is too large, it is not conducive to cost control, and due to the absorption, scattering and other losses of the film layer, after the film system reaches a certain number of layers, continuing to increase the number of film layers will no longer increase its reflectivity, but it performs well in the UV aging test results, and the attenuation is also within 3%.

[0125] It can be seen from Examples 1 and 6-7 that if the refractive index of each L is too large or the refractive index of each H is too small, the interference principle of light cannot be satisfied. On the contrary, the short-circuit current and fill factor drop significantly, which may be related to the reduction in transmittance in the visible light band.

[0126] It can be seen from Example 1 and Comparative Example 1 that if no UV blocking layer is provided, a significant decrease in component efficiency will occur during the UV aging process.

[0127] It can be seen from Example 1 and Comparative Example 2 that if L is not provided in the film stack structure, the UV blocking layer becomes a single-layer reflective film, and the reflection effect of the single-layer film is limited, showing a slightly lower attenuation than Comparative Example 1. In particular, from the reflectivity calculation formula of the optical element coated with a single-layer film when light is vertically incident, it can be seen that the greater the refractive index of the film layer, the greater the reflectivity, but the refractive index of the film layer in practice is limited, and the highest reflectivity that can be achieved by a single-layer film will not exceed 50%.

[0128] It can be seen from Example 1 and Comparative Example 3 that if H is not provided in the membrane stack structure, the UV blocking layer becomes a single-layer antireflection film, showing a short-circuit current slightly higher than that of Comparative Example 1, but a greater degree of component efficiency attenuation occurs in the UV aging results.

[0129] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A perovskite solar cell, characterized in that: The perovskite solar cell comprises a stacked glass substrate, a UV blocking layer, a transparent conductive layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer and a back electrode layer; The UV blocking layer is a film stack structure, which includes a plurality of high-refractive index material layers and a plurality of low-refractive index material layers that are cross-stacked.

2. The perovskite solar cell according to claim 1, characterized in that The total number of layers of the membrane stack structure is 10-30 layers; Preferably, the refractive index of each layer of the high refractive index material is 1.9-2.7; Preferably, the refractive index of each layer of the low refractive index material is 1.35-1.6; Preferably, in the film stack structure, the material layers on the side close to the glass substrate and the side close to the transparent conductive layer are both high refractive index material layers.

3. The perovskite solar cell according to claim 1 or 2, characterized in that: The thickness of each layer of the high refractive index material is 10-300nm; Preferably, the thickness of each layer of the low refractive index material is 10-300 nm.

4. The perovskite solar cell according to any one of claims 1 to 3, characterized in that: The material of each layer of the high refractive index material includes any one of metal oxide, metal sulfide or nitride, or a combination of at least two thereof; Preferably, the material of each low refractive index material layer includes any one of cryolite, lanthanum fluoride, magnesium fluoride, sodium aluminum hexafluoride or SiO2, or a combination of at least two thereof.

5. The perovskite solar cell according to any one of claims 1 to 4, characterized in that: The glass substrate comprises ultra-clear float glass; Preferably, the material of the transparent conductive layer includes any one of ITO, AZO, IWO or IZO or a combination of at least two thereof; Preferably, the thickness of the transparent conductive layer is 15-200 nm; Preferably, the back electrode layer is a metal electrode; Preferably, the thickness of the back electrode layer is 15-100 nm.

6. The perovskite solar cell according to any one of claims 1 to 5, characterized in that: The first charge transport layer and the second charge transport layer transport charges of opposite electrical properties; Preferably, the first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer; Preferably, the thickness of the hole transport layer is 15-45 nm; Preferably, the thickness of the electron transport layer is 5-100 nm; Preferably, the chemical formula of the perovskite absorption layer is ABX3, wherein A includes any one or a combination of at least two of formamidinium ions, methylamine ions or cesium ions, B includes lead ions, and X is a halogen ion; Preferably, the thickness of the perovskite absorption layer is 300-500 nm.

7. A method for preparing a perovskite solar cell according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: A UV blocking layer, a transparent conductive layer, a first charge transport layer, a perovskite absorption layer, a second charge transport layer and a back electrode layer are sequentially deposited on a glass substrate to obtain the perovskite solar cell.

8. The preparation method according to claim 7, characterized in that: The deposition method of the UV blocking layer includes any one of electron beam evaporation, metal organic chemical vapor epitaxy, plasma enhanced vapor deposition, magnetron sputtering, atomic layer deposition, reactive plasma deposition, solution method or vacuum thermal evaporation, or a combination of at least two thereof; Preferably, the deposition method of the transparent conductive layer includes reactive plasma deposition and / or magnetron sputtering; Preferably, the deposition method of the back electrode layer includes vacuum thermal evaporation and / or magnetron sputtering.

9. The preparation method according to claim 7 or 8, characterized in that: The preparation method of the perovskite absorption layer includes any one of a solution method, a doctor blade method, a spray method, an inkjet printing method, a printing method or a vacuum solution two-step method; Preferably, in the scraping method, the scraping rate is 10-15 mm / s.

10. A photovoltaic module, characterized in that: The photovoltaic module comprises the perovskite solar cell according to any one of claims 1 to 6.